2022
DOI: 10.1007/s11356-021-18358-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immunomodulatory efficacy of rosemary and fenugreek against Escherichia coli infection via suppression of inflammation and oxidative stress in broilers

Abstract: Broilers are frequently infected with Escherichia coli (E.Coli) bacteria, which often leads to the emergence of many diseases and high economic losses. Hence, the present study was performed to assess the comparative e cacy of dietary rosemary and fenugreek, under E.Coli-infection in broilers, via evaluation of growth performance, biochemical indices, immunological response and histo-morphological changes.Eighty Cobb broilers were allotted to four equal groups (n=20 chicks/group); control non-infected (CN), co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Lee et al (2019) [182] noted that 1,8-cineole of laurel leaves reduced the expression of proinflammatory cytokines by suppressing NLRP3 inflammasome activation. Farouk et al (2022) [183] reported a significant increase in immunoglobulin G with a significant decline in IL-6 level in broilers treated with rosemary leaf powder (5 g/kg ration). Tsai et al (2013) [184] reported that ethanolic rosemary extract treatment, in the progression of inflammation, significantly suppressed the secretion and mRNA expression of proinflammatory cytokines, including IL-1β and TNF-α, due to diminished nuclear factor kappa-B (NF-κB) activation and Toll-like receptor (TLR2) mediated signaling pathways.…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%
“…Lee et al (2019) [182] noted that 1,8-cineole of laurel leaves reduced the expression of proinflammatory cytokines by suppressing NLRP3 inflammasome activation. Farouk et al (2022) [183] reported a significant increase in immunoglobulin G with a significant decline in IL-6 level in broilers treated with rosemary leaf powder (5 g/kg ration). Tsai et al (2013) [184] reported that ethanolic rosemary extract treatment, in the progression of inflammation, significantly suppressed the secretion and mRNA expression of proinflammatory cytokines, including IL-1β and TNF-α, due to diminished nuclear factor kappa-B (NF-κB) activation and Toll-like receptor (TLR2) mediated signaling pathways.…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%
“…Fenugreek ( Trigonella foenum graecum L.) is a member of the Fabaceae family that has been used in folk medicine for centuries to treat a variety of ailments [ 167 , 168 ]. It exhibits antioxidant and antimicrobial functions, anti-cancer activity, anti-diabetic, anti-atherosclerotic, immunomodulatory, and anti-aflatoxin effects [ 169 , 170 , 171 ]. Fenugreek has been shown to exert hepatoprotective and nephroprotective effects by reducing lipid peroxidation levels in the liver and kidney, in addition to enhancing cellular antioxidant defense in rats [ 172 , 173 , 174 ].…”
Section: Herbal Productmentioning
confidence: 99%
“…(Salvia rosmarinus) is a Mediterranean plant that is now widely available in several countries [5,6]. Rosemary extract can be used to treat inflammation-related diseases [7].…”
Section: Rosemarymentioning
confidence: 99%